Peran Guru dalam Menerapkan Deep Learning di Sekolah Dasar - Nuryadi, Fakhri Hannan; Setiawan, Fajar; Faradita, Meirza Nanda (LPPM Universitas PGRI Argopuro Jember, 2026)
This study aims to: (1) Describe elementary school teachers' understanding of the concept of Deep Learning, considering that this conceptual understanding is the main foundation for transformative pedagogical practice; (2) Describe the forms of roles that are clearly displayed by teachers in the learning process to encourage the occurrence of Deep Learning, which includes the principles of awareness, meaningfulness, and encouraging; and (3) Describe the supporting and inhibiting factors faced by teachers in implementing these roles, which include internal aspects (individual capacity) and external aspects (school policy support and availability of resources). The research uses a qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews with three classroom teachers (II, IV, VI), three representative students, and the principal, and document studies. The data analysis technique follows an interactive model through data reduction, data presentation, and conclusion drawn. The research revealed that: (1) Teachers' understanding of deep learning develops progressively according to the class level, from meaning as applicable knowledge to the formation of mindset; (2) The role of teachers is shown through a variety of strategies—the principles of awareness (question-and-answer techniques, reflection journals), meaningful (simulation, collaborative projects), and exhilarating (play-based learning, intellectual challenges); (3) The main supporting factors include teacher commitment and instructional leadership, while the main obstacles are administrative burden and curriculum pressure. Teachers have demonstrated a comprehensive understanding of deep learning and are able to apply the role of facilitators through strategies that are differentiated according to the grade level. The success of deep learning implementation is highly dependent on systemic support in reducing administrative barriers and strengthening teacher capacity through sustainable development programs.